A randomized, double-blind trial investigating the efficacy of caspofungin versus amphotericin B deoxycholate in the treatment of invasive candidiasis in neonates and infants younger than 3 months of age. (5th October 2019) - Kim, Jason; Nakwa, Firdose Lambey; Araujo Motta, Fábio; Liu, Hong; Dorr, Mary Beth; Anderson, Leah J; Kartsonis, Nicholas
Abstract: Objectives: Investigate the efficacy of caspofungin in participants <3 months of age with invasive Candida infection (ICI). Methods: This multicentre, randomized, double-blind, comparator-controlled, Phase 2 study (protocol MK0991-064; NCT01945281) enrolled participants <3 months of age with culture-confirmed ICI within 96 h of study entry. Participants were randomly assigned 2:1 to once-daily intravenous 2 mg/kg caspofungin or intravenous 1 mg/kg amphotericin B deoxycholate (dAMB). The primary endpoint was fungal-free survival (FFS) 2 weeks after treatment in the full-analysis-set (FAS) population, defined as participants with culture-confirmed ICI who received ≥1 dose of therapy. Planned enrolment was 90 participants. Results: Fifty-one participants were enrolled; 49 received treatment (caspofungin, n =33; dAMB, n =16); 2 additional participants did not have confirmed infections at study entry. The study was terminated after ∼ 3.5 years because of low enrolment. Forty-seven participants were included in the FAS population (caspofungin, n =31; dAMB, n =16). FFS rate at 2 weeks after treatment was 71.0% (22/31) in the caspofungin arm and 68.8% (11/16) in the dAMB arm [difference, stratified by weight, − 0.9% (95% CI, − 24.3%–27.7%)]. Adverse events developed in 84.8% (28/33) of participants in the caspofungin arm and 100% (16/16) in the dAMB arm. Conclusions: Among neonates and infants with confirmed ICI, FFS at 2 weeks was similar in the caspofungin and dAMB treatment arms. A smaller proportion of participants who received caspofungin experienced adverse events.